CVD risk factors and surrogate markers - Urban-rural differences - Joel Nuotio; Lauri Vähämurto; Katja Pahkala; Costan G. Magnussen; Nina Hutri-Kähönen; Mika Kähönen; Tomi Laitinen; Leena Taittonen; Päivi Tossavainen; Terho Lehtimäki; Eero Jokinen; Jorma S.A. Viikari; et al. (SAGE PUBLICATIONS LTD, 2022)
Aims: Disparity in cardiovascular disease (CVD) mortality and risk factor levels between urban and rural regions has been confirmed worldwide. The aim of this study was to examine how living in different community types (urban-rural) in childhood and adulthood are related to cardiovascular risk factors and surrogate markers of CVD such as carotid intima-media thickness (IMT) and left ventricular mass (LVM).
Methods: The study population comprised 2903 participants (54.1% female, mean age 10.5 years in 1980) of the Cardiovascular Risk in Young Finns Study who had been clinically examined in 1980 (age 3-18 years) and had participated in at least one adult follow-up (2001-2011).
Results: In adulthood, urban residents had lower systolic blood pressure (-1 mmHg), LDL-cholesterol (-0.05 mmol/l), lower body mass index (-1.0 kg/m(2)) and glycosylated haemoglobin levels (-0.05 mmol/mol), and lower prevalence of metabolic syndrome (19.9 v. 23.7%) than their rural counterparts. In addition, participants continuously living in urban areas had significantly lower IMT (-0.01 mm), LVM (1.59 g/m(2.7)) and pulse wave velocity (-0.22 m/s) and higher carotid artery compliance (0.07%/10 mmHg) compared to persistently rural residents. The differences in surrogate markers of CVD were only partially attenuated when adjusted for cardiovascular risk factors.
Conclusions: Participants living in urban communities had a more favourable cardiovascular risk factor profile than rural residents. Furthermore, participants continuously living in urban areas had less subclinical markers related to CVD compared with participants living in rural areas. Urban-rural differences in cardiovascular health might provide important opportunities for optimizing prevention by targeting areas of highest need.